Pengujian Zeolit Alam Mordenit Sebagai Penjerap Proses Pendegradasian Kandungan Amonium di dalam Air Tambak - Nuryoto, Nuryoto; Kurniawan, Teguh; Kustiningsih, Indar (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTIndonesia has an abundant quantity of natural zeolites that have not yet been utilized maximally. On the other hand, fishpond farmers have a problem regarding the presence of ammonium in the fishpond water which will negatively impact to survival of fish, especially small fish. To solve this problem, this research was utilizing natural zeolite to degrade ammonium in the fishpond water. This research aimed to test mordenite natural zeolite from Bayah as an adsorbent to collaborate some variables impact to reach more maximal adsorption. The variables that were used to be observed were: mordenite natural zeolite from Bayah as an adsorbent which has been activated by 1-7 N H2SO4Ã‚Â and the other was without activation, ammonium concentration of 80-800 ppm, the particle size of adsorbent of 80 and 150 mesh, stirring speed of 600 and 800 rpm, and without stirring by duration adsorption time of 60 minutes. The research results showed that mordenite natural zeolite after activated was able to adsorb of 100% ammonium, while for the mordenite natural zeolite from Bayah without stirring was of 80%, by the same absorption time. These results will give significant benefits for fishpond farmers to increase their productivity because of the increase in fish survival.Keywords: adsorption, adsorbent, zeolite, amoniumABSTRAKKandungan zeolit alam di Indonesia cukup melimpah dan belum termanfaatkan secara maksimal. Pada sisi lain petani tambak dihadapkan pada masalah terdapatnya kandungan amonium di dalam air tambak, yang akan berdampak negatif bagi keberlangsungan hidup ikan, terutama ikan yang masih kecil. Penelitian ini mencoba memanfaatkan zeolit alam guna mendegradasi kandungan amonium dalam air tambak. Tujuan penelitian ini adalah melakukan pengujian terhadap zeolit alam mordenit dari Bayah sebagai adsorben, baik dilakukan dengan pengadukan maupun tanpa pengadukan, serta mengkolaborasi beberapa variabel yang berpengaruh agar hasil adsorpsi lebih maksimal. Observasi dilakukan dengan zeolit alam mordenit dari Bayah yang telah diaktivasi dengan 1-7 N H2SO4Ã‚Â maupunÃ‚Â tanpa aktivasi, rentang konsentrasi larutan amonium 80-800 ppm, ukuran partikel adsorben 80 dan 150 mesh, kecepatan pengadukan 600 dan 800 rpm, dan tanpa pengadukan serta lamanya waktu penyerapan 60 menit. Hasil penelitian menunjukan hasil yang sangat baik, dan secara umum zeolit alam mordenit Bayah teraktivasi telah mampu melakukan adsorpsi amonium sebesar 100%, sedangkan untuk zeolit alam mordenit Bayah tanpa pengadukan sebesar 80% pada waktu adsorpsi yang sama.Kata kunci: adsorpsi, adsorben, zeolit, amonium